Postpartum TDF continuation in high HBV-DNA mothers: safety for breastfeeding and enhanced infant immunity - Han, Dongxiang; Gen, Xiao; Wang, Wei; Du, Jianxiu; Chu, Weisha; Xiao, Hua; Zhang, Yan (Frontiers in Pediatrics, 2026)
BackgroundHigh HBV-DNA load in pregnant women increases the risk of vertical transmission to infants. Tenofovir disoproxil fumarate (TDF) is an effective antiviral treatment, but its safety and efficacy in breastfeeding mothers with high HBV-DNA loads remain unclear.MethodsThis retrospective cohort study included 210 high HBV-DNA load mothers, divided into a TDF-BF Group (n = 110) that continued TDF postpartum and breastfed, and a Non-TDF-BF Group (n = 100) that discontinued TDF postpartum but breastfed. Primary outcomes were HBV transmission, infant HBV serostatus, neonatal safety outcomes, and maternal outcomes.ResultsThe TDF-BF Group had significantly lower rates of vertical HBV transmission (P < 0.05) and HBsAg positivity at 12 months (P < 0.05) compared to the Non-TDF-BF Group. A higher proportion of infants in the TDF-BF Group had protective levels of anti-HBs at 12 months (P = 0.046, indicating borderline significance). Infant safety outcomes related to growth were comparable between groups, but the TDF-BF Group had significantly higher serum creatinine levels and lower serum phosphate levels (all P < 0.05, raising a potential signal for renal function differences). Maternal outcomes favored the TDF-BF Group, with better HBV-DNA suppression and ALT normalization.ConclusionPostpartum continuation of TDF and breastfeeding is an effective and safe strategy for reducing vertical HBV transmission and promoting infant immunity in high HBV-DNA load mothers. Notably, Tenofovir was not detected in the infant plasma, supporting the safety of this approach.